Forgiveness and Psychological Well-Being in Adolescent Victims of Domestic Violence - Rey Anggita Laurance Suparman; Arthur Huwae (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Family is the safest place for children, but often, some children feel the opposite. Ironically, the family is sometimes a place where violence occurs, which is often known as domestic violence. This violence does not only happen to wives but can also happen to children and even teenagers, both men and women. Adolescents who experience violence in the family will have poor physical and psychological health, making it difficult for them to forget or even forgive the events they experienced. This research aims to determine the relationship between forgiveness and psychological well-being, especially for adolescent victims of domestic violence. The type of research used is quantitative with a correlational design. A total of 42 teenage victims of domestic violence became participants using purposive sampling techniques. The measuring tool in this research is the Enright Forgiveness Inventory. The research results show that there is a significant positive correlation between forgiveness and psychological well-being in adolescent victims of domestic violence. These results indicate that forgiveness is one of the factors that influences the psychological well-being of adolescent victims of domestic violence. This means that when there is an increase in forgiveness, psychological well-being will increase, and vice versa.